Transition from Legal Education to Practice: Extra-Curricular Competitions offer the Missing Link - Madeleine Fraser; Joanna MacKenzie; David Wiesbrat; Wesley Tan (Legal Education Review, 2013)
Students, or at least most students, do not come to classes having read the set passages of textbooks and other reading material allocated as preparatory reading for that class. Part II of this article considers whether and why reading is important for the ‘digital native’ generation of law students; Part III canvasses the question whether it is the job of the law academic to motivate law students to do their reading; Part IV explores the reasons for student noncompliance with set reading; and Part V suggests ways in which law teachers can reconcile intergenerational differences on the value of prescribed law school reading, using specific motivational strategies to initiate and sustain a ‘virtuous circle’ of reading behaviour.